Vexibia Alopecroides - How to New Source for the Synthesis of Physiologically Active Substances Used in Medicine (Global Scientific Review, 2023)
This work is devoted to the isolation of Vexibia alopecia des from the Fabacea family e physiologically active flavonoids and the possibility of synthesizing drugs used in medicine on their basis. As a result of the work, a flavonoid was isolated – in exibinol, its structure and properties were studied, and identified by IR, UV, PMR, NMR 13 methods of analysis.